2023
DOI: 10.1051/0004-6361/202245427
|View full text |Cite
|
Sign up to set email alerts
|

Relation between metallicities and spectral energy distributions of Herbig Ae/Be stars

Abstract: Context. Most studies devoted to Herbig Ae/Be stars (HAeBes) assume solar metallicity. However, the stellar metallicity, [M/H], is a fundamental parameter that can strongly differ depending on the source and may have important implications for planet formation. It has been proposed that the deficit of refractory elements observed in the surfaces of some HAeBes may be linked to the presence of cavities in their disks and is likely caused by Jovian planets that trap the metal-rich content. Aims. This work aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 75 publications
1
1
0
Order By: Relevance
“…Additionally, Stapper et al (2022) found that the group I disks have higher dust masses than the group II disks, with the group II disks potentially unable to form giant planets at large radii, resulting in efficient radial drift and compact disks. This agrees with the interpretation of Kama et al (2015) and Guzmán-Díaz et al (2023), who found that refractory elements were depleted in the photospheres of group I objects relative to group II disks, suggesting dust trapping in group I disks by giant planets. The dust mass difference is the source of the difference in the M  -M disk relationship, as the accretion rates have been found to consistent between group I and II systems (Mendigutía et al 2012;Banzatti et al 2018;Grant et al 2022).…”
Section: Making Sense Of the Outlierssupporting
confidence: 92%
“…Additionally, Stapper et al (2022) found that the group I disks have higher dust masses than the group II disks, with the group II disks potentially unable to form giant planets at large radii, resulting in efficient radial drift and compact disks. This agrees with the interpretation of Kama et al (2015) and Guzmán-Díaz et al (2023), who found that refractory elements were depleted in the photospheres of group I objects relative to group II disks, suggesting dust trapping in group I disks by giant planets. The dust mass difference is the source of the difference in the M  -M disk relationship, as the accretion rates have been found to consistent between group I and II systems (Mendigutía et al 2012;Banzatti et al 2018;Grant et al 2022).…”
Section: Making Sense Of the Outlierssupporting
confidence: 92%
“…YSOs can be more dependent on the presence of giant planets than on time (see Pinilla et al 2022;Rich et al 2022;Stapper et al 2022Stapper et al , 2023Guzmán-Díaz et al 2023), and although it is likely that the accretion rate decreases with time, episodic accretion seems to be the norm (Fischer et al 2023;Grant et al 2023).…”
Section: Clustering Properties Of the More-massive Ysos (M >mentioning
confidence: 99%